Hank the Cowdog: Wagons West - Book 67 - Erickson, John R.; 1943-; Holmes, Gerald L. (Maverick Books, Inc., 2016)
"It's early springtime on the ranch, and Hank is going through the usual motions of making sure that a warm spring arrives safely: singing songs about it, barking faithfully each morning, and helping the cowboys with their work around the ranch. However, in the midst of a particularly hard day's nap, he receives a report that his little birdy friend, Madame Moonshine, is in danger of being eaten by Pete the Barncat"--
Keywords: Fiction; Fiction; Ranch life; Fiction; Dogs; Hank the Cowdog (Fictitious character); Dogs; Ranch life; Juvenile fiction; Juvenile fiction; Hank the Cowdog (Fictitious character); Juvenile fiction